A Computerized System to Solve Difficulties in Finding Medicines under the Medicine Shortages in Sri Lanka - B.B. Punchihewa; B.M.S.L. Bandaranayaka; G.S. Premachandra; D. I. De Silva; S.P. Vidhanaarachchi (International Journal of Engineering and Management Research, 2022)
Due to ongoing financial crisis in Sri Lanka, patients are starting to suffer from medicine shortages at an increasing rate. Patients are having to go to multiple pharmacies to find certain medicines which could result in health complications. Although e-pharmacy platforms provide the functionality to order medicines by uploading the prescription sheet, they do not provide alternatives on where to find the medicines that are not available in the pharmacy. This research introduces a new functionality to provide patients suggestion on where exactly to find missing medicines. This is found through checking the stock availability of the medicine in other pharmacies in sorted order with respect to the delivery location of the patient taken via Google map API to make the process much more efficient and practical. This is achieved by implementing a global identifier for each medicine where all pharmacies keep the records of the medicines in reference to the defined global identifier of that medicine. In addition to that, the system allows patients to view all the pharmacies nearest to their delivery location and give the freedom to place orders to whichever pharmacy they prefer. If a medicine is not available in the pharmacy which the order was placed for, the system will give suggestions to the patient on where exactly to buy the medicine.